Characterising HIV transmission risk among US patients with HIV in care: a cross-sectional study of sexual risk behaviour among individuals with viral load above 1500 copies/mL. (2nd November 2017) - Stirratt, Michael J; Marks, Gary; O'Daniels, Christine; Cachay, Edward R; Sullivan, Meg; Mugavero, Michael J; Dhanireddy, Shireesha; Rodriguez, Allan E; Giordano, Thomas P
Abstract : Objectives: Viral load and sexual risk behaviour contribute to HIV transmission risk. High HIV viral loads present greater transmission risk than transient viral 'blips' above an undetectable level. This paper therefore characterises sexual risk behaviour among patients with HIV in care with viral loads>1500 copies/mL and associated demographic characteristics. Methods: This cross-sectional study was conducted at six HIV outpatient clinics in USA. The study sample comprises 1315 patients with HIV with a recent viral load >1500 copies/mL. This study sample was drawn from a larger sample of individuals with a recent viral load >1000 copies/mL who completed a computer-assisted self-interview (CASI) regarding sexual risk practices in the last 2 months. The study sample was 32% heterosexual men, 38% men who have sex with men (MSM) and 30% women. Results: Ninety per cent of the sample had their viral load assay within 60 days of the CASI. Thirty-seven per cent reported being sexually active (vaginal or anal intercourse) in the last 2 months. Most of the sexually active participants reported always using condoms (56.9%) or limiting condomless sex to seroconcordant partners (serosorting; 29.2% overall and 42.9% among MSM). Among sexually active participants who reported condomless anal or vaginal sex with an at-risk partner (14%), most had viral loads>10 000 copies/mL (62%). Conclusions: A relatively small number of patients with HIV in care with viral loads above 1500 copies/mL reported concurrent sexual transmission risk behaviours. Most of the individuals in this small group had markedly elevated viral loads, increasing the probability of transmission. Directing interventions to patients in care with high viral loads and concurrent risk behaviour could strengthen HIV prevention and reduce HIV infections. Trial registration number: NCT02044484, completed.